The chemosensory world of mosquitoes: olfactory receptors and their role in blocking mosquito-borne disease transmission - Sitian Xiong; Jingjing Liang; Shuyang Gao; Zhilong Liu; Hong Zheng; Xuesen Yang; Ying Wang; Shasha Yu (Parasites & Vectors)
Abstract Mosquitoes are vectors for a variety of infectious diseases, which pose a significant threat to human health, public well-being, and national security. The increasing prevalence of insecticide resistance has further complicated efforts to control these diseases, highlighting the urgent need for innovative strategies to block their transmission. The mosquito olfactory system, which mediates a wide range of behaviors throughout the mosquito's life cycle, including host-seeking, foraging, oviposition, mating, avoidance behavior, and social communication, offers a promising avenue for intervention. Specifically, olfactory receptors play a crucial role in enabling female mosquitoes to locate human hosts through odor recognition, a process that facilitates the transmission of pathogens responsible for diseases such as malaria and dengue fever. Understanding the roles of these receptors in different mosquito behaviors, their mechanisms of odor recognition, and their involvement in disease transmission could provide valuable insights for developing new mosquito control strategies that target olfactory receptors to effectively block disease spread. This review aims to provide a comprehensive summary of the mosquito olfactory system, including its composition, the mechanisms of action of olfactory receptors, their interactions with repellents, and their potential role in the prevention and control of mosquito-borne diseases. Graphical Abstract